From carbon nanotubes and silicate layers to graphene platelets for polymer nanocomposites - Zaman, Izzuddin; Kuan, Hsu-Chiang; Dai, Jingfei; Kawashima, Nobuyuki; Michelmore, Andrew; Sovi, Alex; Dong, Songyi; Luonga, Lee; Ma, Jun (The Royal Society of Chemistry, 2012)
In spite of extensive studies conducted on carbon nanotubes and silicate layers for their polymer-based nanocomposites, the rise of graphene now provides a more promising candidate due to its exceptionally high mechanical performance and electrical and thermal conductivities. The present study developed a facile approach to fabricate epoxy–graphene nanocomposites by thermally expanding a commercial product followed by ultrasonication and solution-compounding with epoxy, and investigated their morphologies, mechanical properties, electrical conductivity and thermal mechanical behaviour. Graphene platelets (GnPs) of 3.57